Profil Komunikasi Matematika Tulis Siswa SMP dalam Memecahkan Masalah Matematika Ditinjau dari Kepribadian Extrovert dan Introvert - Dwi Permatasari; Rini Setianingsih (JRPM (Jurnal Review Pembelajaran Matematika), 2021)
Communication is important in mathematics learning. This study aims to describe the written mathematics communication profile of junior high school students in solving mathematics problems reviewed from extrovert-introvert personality. The subjects of this study consist of one introvert student and one extrovert student, while the instruments used were the Myers Briggs Type Indicators personality questionnaire, math ability tests, and written mathematics communication tests. The results of this study revealed that introvert student fulfilled the accuracy and completeness aspect at the stage of understanding the problems, devising a plan, and carrying out the plan. Meanwhile, the extrovert students fulfill the accuracy aspect only at the stage of understanding the problem. Besides that, extrovert students fulfill the completeness aspect at the stage of carrying out the plan and looking back. Introvert and extrovert students do not fulfill the fluency aspect. So that introvert students' written mathematics communication is better than extrovert students.